Performance Assessment of a Semi-Circular Breakwater through CFD Modelling - Gomes, Ana (2020)
Coastal defence works, such as breakwaters, are structures that aim to support the action of waves and dissipate their energy. Therefore, they provide conditions for stabilizing the coast, protecting ports, beaches and other coastal infrastructures and ecosystems. Semicircular breakwaters have been applied in di erent locations around the world due to their aesthetic advantages and high structural performance. Marine structures are subject to hydrodynamic actions normally estimated through physical models. However, these models are complex to implement, involving high costs and long experimental procedures. Thus, alternative methodologies for studying the hydrodynamic performance of these structures are of great use. This work presents the results of the application of a computational fluid dynamics (CFD) tool to study the stability of a perforated semicircular breakwater, based on a rubble mound foundation. The model was validated against experimental results of the critical weight necessary to resist sliding, taking into account the e ects of water depth and di erent characteristics of the waves. A comparison is made between the perforated and the non-perforated solution in terms of the breakwater’s performance to dissipate wave energy. Dissipation conditions of this energy, in the exposed face, are also evaluated in detail, in order to assess the potential of this structure as a biological refuge for marine species. Both solutions show similar performance in terms of results obtained for the wave reflectivity coe cient. The turbulence dissipation on the exposed face of the perforated breakwater is limited to a region of restricted extension around it, which is advantageous in terms of the passage of species into the breakwater.